PENGARUH LINGKUNGAN BELAJAR TERHADAP TINGKAT KONSENTRASI BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MATQ AL-MATIN - Aulia Safitri (JURNAL ISLAMIKA, 2026)
Maintaining students’ focus and concentration is an important challenge in modern Islamic education, which requires a balance between general knowledge and religious values. This study was conducted to determine the influence of the learning environment on students’ concentration levels in the Akidah Akhlak subject at MATQ Al-Matin. The research employed an ex post facto design with a quantitative approach and simple linear regression analysis. The sample consisted of 61 students from grades X and XI, selected through purposive sampling. Data were collected through questionnaires that had been tested for validity and reliability, supported by observations and documentation. The results of the analysis showed that the learning environment has a positive and significant effect on students’ concentration, with the regression equation Y = 2.729 + 0.733X and a significance value of 0.000 (p < 0.05). These findings indicate that a conducive learning environment physically, socially, and spiritually can improve students’ focus and learning effectiveness. This study implies the importance of creating a comfortable and structured learning atmosphere in Islamic educational institutions, especially pesantren, to support the optimization of students’ concentration and learning outcomes. Keywords: learning concentration, learning environment, Islamic education, pesantren